Room-Temperature Stimulated Emission and Lasing in Recrystallized Cesium Lead Bromide Perovskite Thin Films - Pourdavoud, Neda (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 The Authors. Published by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.